1978
DOI: 10.1212/wnl.28.6.545
|View full text |Cite
|
Sign up to set email alerts
|

Lesion localization in aphasia with cranial computed tomography and the Boston Diagnostic Aphasia Exam

Abstract: Nineteen stable left-hemisphere stroke patients with aphasia were evaluated by the Boston Diagnostic Aphasia Examination (BDAE) and the Token Test (TT), and by cranial computed tomography (CT). The types of aphasia included Broca (three patients), Wernicke (four patients), conduction (four patients), transcortical motor (four patients), and global (four patients). The lesions, as localized by CT scan, were superimposed onto five composite lesion localization maps for these five aphasia syndromes. There was goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…Each lesion map was realigned into stereotaxic Montreal Neurological Institute (MNI) space to overlay them on standard brain templates. In order to improve the lesion-mapping method, the following procedures were followed: an experienced examiner mapped all of the lesions, and these lesion maps were reviewed by a 2 nd rater following procedures previously described to generate the final lesion maps (Cola, Daniels, Corey, Lemen, Romero, & Foundas, 2010; Daniels & Foundas, 1999; Foundas, Daniels, Vasterling, 1998; Hanna-Pladdy et al, 2001; Naeser & Hayward, 1978; Damasio & Damasio, 1989). …”
Section: Methodsmentioning
confidence: 99%
“…Each lesion map was realigned into stereotaxic Montreal Neurological Institute (MNI) space to overlay them on standard brain templates. In order to improve the lesion-mapping method, the following procedures were followed: an experienced examiner mapped all of the lesions, and these lesion maps were reviewed by a 2 nd rater following procedures previously described to generate the final lesion maps (Cola, Daniels, Corey, Lemen, Romero, & Foundas, 2010; Daniels & Foundas, 1999; Foundas, Daniels, Vasterling, 1998; Hanna-Pladdy et al, 2001; Naeser & Hayward, 1978; Damasio & Damasio, 1989). …”
Section: Methodsmentioning
confidence: 99%
“…Specifically, several studies have shown that Broca’s aphasia is caused by lesions involving the insula, white matter underlying Broca’s area, surrounding frontal cortex, basal ganglia, and superior temporal lobe, rather than Brodmann’s areas 44 and 45 proper. 10,20,25,26,32 Furthermore, the brains Broca examined himself have been reevaluated with CT and MRI, 10 showing damage extending far beyond the inferior frontal gyrus: in the claustrum, putamen, caudate, globus pallidus, internal and external capsules, superior temporal lobe, the entire insula, and the inferior parietal lobe in Leborgne’s brain, for example.…”
Section: Discussionmentioning
confidence: 99%
“…29,31 But there is a high variability in the location of these speech arrest sites that cannot be definitively predicted by anatomical features. 26 And in many patients (up to 40%), no frontal lobe speech arrest sites can be found. 31 Why some patients have clear speech arrest in Broca’s area and others do not is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the earliest applications of this approach to disorders of spoken language understanding, Kertesz, Lesk, and McCabe (1977) and Naeser and Hayward (1978) overlaid the lesions of patients with Wernicke's aphasia. Both studies demonstrated consistent involvement of the left superior temporal gyrus.…”
Section: Historical Backgroundmentioning
confidence: 99%